The first time I saw him [large type] - Dave, Laura (Center Point Large Print, 2026)
"Five years after her husband, Owen, disappeared, Hannah Hall and her stepdaughter, Bailey, have settled into a new life in Southern California. Together, they've forged a relationship with Bailey's grandfather, Nicholas, and are putting the past behind them. But when Owen shows up at Hannah's new exhibition, she knows that she and Bailey are in danger again. As a thrilling drama unfolds, Hannah and Bailey are forced to go on the run in a relentless race to keep their past from catching up with them. Hannah risks everything to get Bailey to safety--and finds there just might be one way back to Owen. The First Time I Saw Him picks up right where the epilogue for ... The Last Thing He Told Me left off ..."--